2009
DOI: 10.1002/0471142301.ns0932s49
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation and Reversal of a Persistent Depression‐like Syndrome in Rodents

Abstract: Alterations in multiple biological functions, such as transcription factor activity, are implicated in the neurobiology of depression based primarily on the characterization of antidepressant efficacy in naïve rodents rather than on models that capture the protracted feelings of anhedonia and helplessness that typify depression. In order to address this issue, the authors developed protocols in rats and mice calling for chronic oral exposure to the stress-associated adrenal hormone, corticosterone (CORT), resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 39 publications
9
138
0
Order By: Relevance
“…However, this is the first study to show decreased mGluR5 expression in the nucleus accumbens following CORT exposure, and this finding adds to the growing literature identifying neuroadaptations within this brain region as a consequence of CORT or repeated stressor exposure (Campioni et al, 2009;Gourley and Taylor, 2009;Lemos et al, 2012;Morales-Medina et al, 2009;Perrotti et al, 2004;Shoji and Mizoguchi, 2010;Tidey and Miczek, 1997). Importantly, the presence of CORT-induced neuroadaptations in mGluR5, as we show here, potentially has broad implications and may be relevant to better understanding some mental health disorders (ie, depression, post-traumatic stress disorder), specifically as chronic CORT exposure is commonly used to induce various behavioral aspects of these disorders (Ardayfio and Kim, 2006;Gourley and Taylor, 2009;Hache et al, 2012;Rainer et al, 2011). Further, this is especially relevant given that pharmacological manipulation of mGluR5 and other mGluRs is of interest as potential therapeutics for the treatment of neuropsychiatric disorders (Krystal et al, 2010;Witkin et al, 2007).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, this is the first study to show decreased mGluR5 expression in the nucleus accumbens following CORT exposure, and this finding adds to the growing literature identifying neuroadaptations within this brain region as a consequence of CORT or repeated stressor exposure (Campioni et al, 2009;Gourley and Taylor, 2009;Lemos et al, 2012;Morales-Medina et al, 2009;Perrotti et al, 2004;Shoji and Mizoguchi, 2010;Tidey and Miczek, 1997). Importantly, the presence of CORT-induced neuroadaptations in mGluR5, as we show here, potentially has broad implications and may be relevant to better understanding some mental health disorders (ie, depression, post-traumatic stress disorder), specifically as chronic CORT exposure is commonly used to induce various behavioral aspects of these disorders (Ardayfio and Kim, 2006;Gourley and Taylor, 2009;Hache et al, 2012;Rainer et al, 2011). Further, this is especially relevant given that pharmacological manipulation of mGluR5 and other mGluRs is of interest as potential therapeutics for the treatment of neuropsychiatric disorders (Krystal et al, 2010;Witkin et al, 2007).…”
Section: Discussionmentioning
confidence: 60%
“…Corticosterone hemisuccinate (4-pregnen-11b, 21-DIOL-3, 20-DIONE 21-hemisuccinate; Steraloids, Newport, RI) was dissolved in tap water by addition of NaOH and neutralized with HCl, to a final pH of 7.0-7.4 (Besheer et al, 2012b;Besheer et al, 2013;Gourley and Taylor, 2009). 3-Cyano-N-(1,3-diphenyl-1H-pyrazol-5-yl)benzamide (CDPPB; Tocris) dose and pretreatment interval were chosen based on the literature (Clifton et al, 2013;Fowler et al, 2011;Gass and Olive, 2009;Stefani and Moghaddam, 2010).…”
Section: Drugsmentioning
confidence: 99%
“…Adult mice (two to three months of age) were given corticosterone (Sigma) in their drinking water (25 mg/l) for 3 weeks, as previously described (Gourley and Taylor, 2009;Teixeira et al, 2011). Mice were tested 1 week after the end of treatment.…”
Section: Corticosterone Treatmentmentioning
confidence: 99%
“…Alterations in multiple biological markers are implicated in the neurobiology of depression, based primarily on the characterization of antidepressant efficacy in naive rodents (Gourley and Taylor, 2009). However, it seems more appropriate to perform pharmacological studies in animal models that exhibit hallmark characteristics of anxiety/depression.…”
Section: Introductionmentioning
confidence: 99%
“…Although UCMS has been efficiently used to assess antidepressant activity (Surget et al, 2009;Farley et al, 2010), it is notoriously difficult to reproduce consistently in rodents. An intriguing alternative may be to supply mice with exogenous corticosterone (David et al, 2009;Gourley and Taylor, 2009), a hormone produced in the adrenal glands in response to stress and found to be elevated in several animal models of depression and in depressed humans (Sterner and Kalynchuk, 2010). We have recently reported, in mice administered with corticosterone, some behavioral abnormalities that are indicative of anhedonia and hopelessness (David et al, 2009) and that mimic depressive symptoms observed in humans (Holsboer, 2000;Nemeroff and Vale, 2005).…”
Section: Introductionmentioning
confidence: 99%